Transitions in the stock markets of the US, UK, and Germany - Matthias Raddant; Friedrich Wagner (Kiel Institute for the World Economy (IfW), 2014)
In this paper we analyze transitions in the stock markets of the US, the UK, and Germany. For all this markets we find that while the markets were focused on stocks from the IT and technology sector around the year 2000, this focus has vanished and the markets have mostly moved towards a focus on stocks from the financial sector. This development is paralleled by changes in the returns distributions and the tail exponent. We show that we can extend the concept of beta values to systematically describe a risk measure for stocks from different sectors of the economy. This slowly varying sector specific risk measure describes ordered states in the market and identifies sectors which show concentration of market risk.
Keywords: G11; G12; 330; stock price correlations; financial risk; CAPM